Catalytic hydroboration of aldehydes, ketones, alkynes and alkenes initiated by NaOH. Issue 17 (15th August 2017) - Wu, Yile; Shan, Changkai; Ying, Jianxi; Su, Jue; Zhu, Jun; Liu, Liu Leo; Zhao, Yufen
Abstract : Commercially available NaOH powder is shown to be an efficient transition-metal-free initiator for the catalytic hydroboration of aldehydes, ketones, alkynes and alkenes with HBpin and 9-BBN under mild conditions. Abstract : Commercially available NaOH powder is shown to be an efficient transition-metal-free initiator for the catalytic hydroboration of aldehydes, ketones, alkynes and alkenes with HBpin and 9-BBN under mild conditions. Combined experimental and theoretical studies suggest that the catalytically active species is a boron hydride generated in situ from the reaction mixture.